The Strategic Role of Teachers and Education Personnel as Marketing Agents for Educational Institutions - Mulawarman, Widyatmke Gede; Yahya, Masrur; Nurlaili; Natavia, Dini Sakti (Al-Qalam Institue, 2025)
In the face of increasing competition among educational institutions, effective marketing strategies have become crucial for enhancing their image and attracting students. This study aims to describe the strategic role of teachers and education personnel as marketing agents in improving the image and competitiveness of educational institutions. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The study subjects were teachers and education personnel at a vocational high school. The study results indicate that teachers and education personnel have an essential role in building public trust in schools through excellent service, effective communication with the community, and active involvement in school promotion. Institutional marketing strategies include student testimonials, educational exhibitions, social media, and the role of teachers in conveying school excellence to the community. This study highlights the importance of teachers and education personnel in shaping public perceptions and promoting school values. It also emphasizes the need to build the capacity of education personnel in public communication and institutional promotion to enhance school reputation and competitiveness.